Associations between Lower-Order Anxiety Sensitivity Facets and PTSD Symptomatology among Trauma-Exposed Firefighters. Issue 2 (March 2022) - Lebeaut, Antoine; Leonard, Samuel J.; Healy, Nathaniel; Raines, Amanda M.; Buser, Sam J.; Vujanovic, Anka A.
Firefighters are chronically exposed to potentially traumatic events, augmenting their risk of developing posttraumatic stress disorder (PTSD). The current study aimed to examine the incremental associations of lower-order dimensions of anxiety sensitivity (AS), examined concurrently, and PTSD symptom severity among a sample of trauma-exposed firefighters. We hypothesized that AS physical and cognitive concerns would be strongly associated with all PTSD symptom clusters and overall symptom severity, after controlling for theoretically relevant covariates (trauma load; years in fire service; alcohol use severity; depressive symptom severity). Participants were comprised of firefighters ( N  = 657) who completed an online questionnaire battery and endorsed PTSD Criterion A trauma exposure. Results revealed that the AS cognitive concerns, but not AS physical concerns, was significantly and robustly associated with overall PTSD symptom severity, intrusion symptoms, and negative alterations in cognitions and mood ( ∆R 2 's = .028–.042; p 's < .01); AS social concerns was incrementally associated with PTSD avoidance ( ∆R 2  = .03, p  < .01). Implications for firefighter-informed, evidence-based interventions are discussed.